Recent progress in developing polymer nanocomposite membranes with ingenious structures for energy storage capacitors. (March 2023) - Huai, Kai; Robertson, Mark; Che, Junbo; Wang, Quan; Liu, Xueqing; Xia, Yuming; Huang, Shuohan; Qiang, Zhe; Zhang, Jianming; Chen, Yuwei
Abstract: Polymer nanocomposite dielectrics (PNDs) have attracted extensive attention due to their excellent mechanical flexibility, ultra-fast charge/discharge rate and low cost. However, conventional membrane processing methods, such as simple physical blending of polymer matrices and fillers, result in PNDs with insufficient energy densities. Recently, developing ingenious structures of membranes used as PNDs has emerged as an important approach to enhance their comprehensive properties. In this review, the recent progress in PNDs for energy storage capacitor applications are reviewed, with a particular focus on optimizing dielectric and energy storage performance through rational structural design of membrane. The effects of microstructural filler designs on dielectric and energy storage properties are discussed in detail, including core-shell structures, hierarchical structures, and other special structures. The preparation methods and performances of PNDs with different macroscopic designs are also systematically discussed. Finally, a brief summary along with some future perspectives on this important research arena are provided. Graphical Abstract: ga1 Highlights: The structural design strategies in polymer nanocomposite dielectrics are systematically summarized. The microstructure designs of fillers for energy storage applications are presented. The macrostructure designs of polymer nanocomposite dielectrics are summarized. Future perspectives are provided to further advance the performance and applications of polymer nanocomposite dielectrics.